Trained Immunity Carried by Non-immune Cells - Hamada, Attoumani; Torre, Cédric; Drancourt, Michel; Ghigo, Eric (Frontiers in Microbiology, 2019)
“Trained immunity” is a term proposed by Netea to describe the ability of an organism to develop an exacerbated immunological response to protect against a second infection independant of the adaptative immunity. This immunological memory can last from one week to several months and is only described in innate immune cells such as monocytes, macrophages and natural killer cells. Paradoxically, the lifespan of these cells in the blood is shorter than the duration of trained immunity. This observation suggested that trained immunity could be carried by long lifespan cells such as stem cells and non-immune cells like fibroblasts. It is now evident that in addition to performing their putative function in the development and maintenance of tissue homeostasis, non-immune cells also play an important role in the response to pathogens by producing anti-microbial factors, with long-term inflammation suggesting that non-immune cells can be trained to confer long-lasting immunological memory. This review provides a summary of the current relevant knowledge about the cells which possess immunological memory and discusses the possibility that non-immune cells may carry immunological memory and mechanisms that might be involved.